A CASE OF COMBINED CENTRAL AND PERIPHERAL DEMYELINATION IN A PATIENT WITH PEDIATRIC MULTIPLE SCLEROSIS AFTER SARS-COV-2 VACCINATION - Gkantzios Aimilios; Kourtesis Ioannis; Barmpari Athanasia; Filippi Aikaterini; Taulant Jupe; Kosta Natalia; Maltezou Maria; Angeloglou Stella; Samaras Nikolasos (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
We present a case of combined central and peripheral demyelination in a patient with pediatric multiple sclerosis after the first dose of ChAdOx1-S (Chimpanzee Adenovirus Oxford 1) vaccination. The patient presented with ascending flaccid quadriparesis with respiratory failure that required mechanical ventilation. The lumbar puncture revealed albuminocytological dissociation, was negative for presence of JCV (John Cunningham Virus) in the CSF (Cerebrospinal Fluid) and ruled out other infections. A few days later he developed anisocoria and multiple new enlarging acute demyelinating lesions in the brain MRI (Magnetic Resonance Imaging). He was treated with intravenous immunoglobulin, corticosteroids and plasma exchange with gradual improvement. All other diseases were excluded via MR Spectroscopy, MR Angiography and serum and CSF laboratory investigations. Seven months later, the patient is under intense physiotherapy and is improving every day.